High-resolution optical coherence tomography demonstration of membranes spanning optic disc pits and colobomas. Issue 3 (9th December 2008) - Doyle, E; Trivedi, D; Good, P; Scott, R A; Kirkby, G R
Abstract : Objectives: To demonstrate the features of optic disc pits and colobomas revealed by high-resolution optical coherence tomography (OCT) and their association with the development of maculopathy. Methods: Subjects with disc pits or colobomas and no other ocular history underwent full ophthalmic examinations including logMAR visual acuity and contrast sensitivity. Fundus photographs and high-resolution OCT images were obtained. Results: Seven patients were identified with optic disc pits or colobomas aged 25 to 63 years. Five patients had a unilateral optic disc pit, one had a unilateral disc coloboma, and another had bilateral disc colobomas. Apart from one eye with a grossly anomalous disc, vision was logMAR 0.4 or better in all eyes. In three of five eyes without maculopathy, a complete membrane could be identified traversing the optic disc cup that was absent or deficient in the three eyes with maculopathy. One patient with optic disc pit and marked schisis-like separation of the retinal layers throughout the macula was asymptomatic with logMAR visual acuity of 0.0 and normal achromatic contrast sensitivity. Conclusions: In this small series of patients with optic disc pits or colobomas, it was possible to identify a membrane spanning the optic disc cup, and it is speculated that this may protect against the development of maculopathy. Schisis-like separation of retinal layers can be associated with normal visual function.